Cerium-based UiO-66 metal–organic frameworks explored as efficient redox catalysts: titanium incorporation and generation of abundant oxygen vacancies. Issue 93 (21st October 2019) - Zhang, Yajun; Chen, Hanjiao; Pan, Yi; Zeng, Xiaoliang; Jiang, Xiaofang; Long, Zhou; Hou, Xiandeng
Abstract : For the first time, UiO-66(Ce) was endowed with greatly improved redox photocatalytic activity via Ti incorporation, based on the formation of oxygen vacancies. Abstract : The recently developed UiO-66(Ce) was firstly endowed with greatly improved redox photocatalytic activity based on titanium incorporation, which for the first time induced the formation of oxygen vacancies in Ce-MOFs, and then promoted the generation of oxidative ˙OH/˙O2 − and reductive electrons.